Era 4.0 Dan Tantangannya Bagi Perpustakaan Perguruan Tinggi Islam Di Indonesia - Rhoni Rodin (Jurnal IPI (Ikatan Pustakawan Indonesia), 2020)
The era of 4.0 is the era of technological industrial revolution which will fundamentally change the paradigm of thinking and how to work. This paper aims to analyze what are the challenges of Islamic higher education libraries in the face of era 4.0. This type of research is a literature study. Literature studies can be obtained from various sources, journals, books, documentation, internet and literature. while analyzing data with descriptive analysis method. The results show that there are several challenges for Islamic higher education libraries in Indonesia in era 4.0, namely libraries not only prioritize traditional roles by providing physical facilities, but more than that the library must also understand the value of the library. The library of Islamic universities in Indonesia in addition to facing very rapid technological developments, also needs to be ready to face changes in user behavior that also change according to the times. The other challenge is the aspect of the university's mission, which is developing and advancing research. The open access movement is also one of the challenges that must be answered immediately by the Islamic university libraries. Then the challenge to accommodate the rapid changes in teaching is also greatly influenced by the development of the use of information technology as it is today.